2015
DOI: 10.1016/j.chb.2014.11.063
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating microblogging (“tweeting”) in higher education: Lessons learnt in a knowledge management course

Abstract: a b s t r a c tThis paper features a competency-enhancing social networking application which provides a solution for the dilemma of non-participating (non-engaged) students in class: 'pedagogical tweeting'. Twitter's micro-blogging service enables both instructors and students to send and read messages (tweets) of up to 140 characters, incl. links to blogs, web pages, photos, videos, etc. As Twitter can be accessed from a website, via applications on PC/Mac, iPhone, Android phones, etc., it represents an effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
82
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(90 citation statements)
references
References 24 publications
6
82
0
2
Order By: Relevance
“…Descriptive results indicate, from instructors' perspectives, communicating with these tools seemed especially beneficial to increase participation among students who might have otherwise been absent and/or shy or quiet during face-to-face class time [21,29]. Among researchers examining synchronous collaboration among primary mathematics students, results indicated that students thoughtfully and successfully engaged in problem solving while participating in a virtual environment [4] and online peer tutoring that improved tutored students' mathematical reasoning skills in addition to personal views about mathematics learning [36].…”
Section: Cluster 4: Mixed Synchronousmentioning
confidence: 99%
See 4 more Smart Citations
“…Descriptive results indicate, from instructors' perspectives, communicating with these tools seemed especially beneficial to increase participation among students who might have otherwise been absent and/or shy or quiet during face-to-face class time [21,29]. Among researchers examining synchronous collaboration among primary mathematics students, results indicated that students thoughtfully and successfully engaged in problem solving while participating in a virtual environment [4] and online peer tutoring that improved tutored students' mathematical reasoning skills in addition to personal views about mathematics learning [36].…”
Section: Cluster 4: Mixed Synchronousmentioning
confidence: 99%
“…Although, the majority of students enrolled in the higher-education blended-learning engineering course reported the SL platform 'better' for motivation, they also reported it 'worse' for concentration [29]. Additionally, although higher-education computer-science students overwhelmingly tweeted constructive comments that encouraged class discussion, there were also examples of students tweeting unrelated comments [21]. Other potential drawbacks to "Mixed Synchronous" CSCL included the additional time communicating via chat took as compared to face-toface interactions [30] and the finding that mixedgender pairing may negatively affect secondary education female achievement in physics problem solving [10].…”
Section: Cluster 4: Mixed Synchronousmentioning
confidence: 99%
See 3 more Smart Citations